COST RECOVERY RATE PROGRAM JAMINAN KESEHATAN NASIONAL BPJS KESEHATAN - Sandra Aulia; Supriadi Supriadi; Dewi Kartika Sari; Arthaingan Mutiha (Department of Accounting-Faculty of Economic and Business (FEB), 2015)
Program Jaminan Kesehatan Nasional (JKN) is an Indonesian public health careprogram organized by Badan Penyelenggara Jaminan Sosial (BPJS). The health care system in thistiered program, all patients are served on the first level health facility and can be referred to moreadvanced facilities. Payments made by the advanced health care facility uses INA CBG's rates.Many parties complaint against the INA CBG's rates that are considered detrimental to thehospital. This study aims to determine whether the INA CBG's rates is profitable by look at costrecovery rate of the tariffs. This study analyzes INA CBGs rates set by the government uses thereal costs incurred hospital. The data collected in this study are primary data and secondary data.This study found that the cost recovery rate is 93% means that hospitals gain 7% by using INACBG's ratesDOI: 10.15408/akt.v8i2.2767